From Pathology to Intervention and Beyond. Reviewing Current Evidence for Treating Trauma-Related Disorders in Later Life - Lely, Jeannette C. G.; Kleber, Rolf J. (Frontiers in Psychiatry, 2022)
Abstract Background. An emerging body of empirical research on trauma-focused interventions for older adults experiencing symptoms of posttraumatic stress disorder or PTSD (APA, 2013) has yielded encouraging results. Nevertheless, up to date, the evidence remains scattered and is developed within rather specific groups, while studies have focused mostly on individual psychopathology, overlooking the relevance of resilience and recovering in one’s social environment. Objective. This study aims at summarizing the emerging evidence on treating trauma-related disorders in older adults, followed by implications for clinical practice and future research. Specifically, the following research questions are addressed: Which factors may optimize access to intervention, what treatment benefits can be realized, and how to improve resilience by using individual as well as community-oriented approaches? Methods. A systematic literature research of intervention studies on PTSD among older adults, published between 1980 and December 2021, was extended by cross-referencing, summarized in a narrative synthesis and supplemented with a clinical vignette reflecting qualitative outcomes. Results. Five RCTs compared varying types of trauma-focused Cognitive Behavioral Therapy with non-trauma-focused control conditions. From one of them, qualitative results were reported as well. The most recent studies reported encouraging results, confirming the suggestion that evidence-based psychotherapy for PTSD can be safely and effectively used with older adults. Conclusions. Since evidence-based psychotherapy for PTSD can be safely and effectively used with older adults, new avenues for practice and research may be found in a resilience perspective and a public mental health framework.